Reactions induced by low energy electrons in cryogenic films - Bass, Andrew D.; Sanche*, Leon (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
We review recent research on reactions (including dissociation) initiated by low-energy electron bombardment of monolayer and multilayer molecular solids at cryogenic temperatures. Withincident electrons of energies below 20 eV, dissociation is observed by the electron stimulated desorption (ESD) of anions from target films and is attributed to the processes of dissociative electronattachment (DEA) and to dipolar dissociation. It is shown that DEA to condensed molecules is sensitive to environmental factors such as the identity of co-adsorbed species and film morphology. The effects of image-charge induced polarization on cross-sections for DEA to CH3Cl are alsodiscussed. Taking as examples, the electron-induced production of CO within multilayer films of methanol and acetone, it is shown that the detection of electronic excited states by high resolution electron energy loss spectroscopy can be used to monitor electron beam damage. In particular, theincident energy dependence of the CO indicates that below 19 eV, dissociation proceeds via the decay of transient negative ions (TNI) into electronically excited dissociative states. The electron induced dissociation of biomolecular targets is also considered, taking as examples the ribose analogtetrahydrofuran and DNA bases adenine and thymine, cytosine and guanine. The ESD of anions from such films also show dissociation via the formation of TNI. In multilayer molecular solids,fragment species resulting from dissociation, may react with neighboring molecules, as is demonstrated in anion ESD measurements from films containing O2 and various hydrocarbon molecules. X-ray photoelecton spectroscopy measurements reported for electron irradiated monolayers of H2O and CF4 on a Si - H passivated surface further show that DEA is an important initial step in the electron-induced chemisorption of fragment species.